Immunomodulatory Effects of Mesenchymal Stem Cells on Drug-Induced Acute Kidney Injury - Han, Qiuxia; Wang, Xiaochen; Ding, Xiaonan; He, Jun; Cai, Guangyan; Zhu, Hanyu (Frontiers in Immunology, 2021)
Drug-induced nephrotoxicity is an important and increasing cause of acute kidney injury (AKI), which accounts for approximately 20% of hospitalized patients. Previous reviews studies on immunity and AKI focused mainly on ischemia-reperfusion (IR), whereas no systematic review addressing drug-induced AKI and its related immune mechanisms is available. Recent studies have provided a deeper understanding on the mechanisms of drug-induced AKI, among which acute tubular interstitial injury induced by the breakdown of innate immunity was reported to play an important role. Emerging research on mesenchymal stem cell (MSC) therapy has revealed its potential as treatment for drug-induced AKI. MSCs can inhibit kidney damage by regulating the innate immune balance, promoting kidney repair, and preventing kidney fibrosis. However, it is important to note that there are various sources of MSCs, which impacts on the immunomodulatory ability of the cells. This review aims to address the immune pathogenesis of drug-induced AKI versus that of IR-induced AKI, and to explore the immunomodulatory effects and therapeutic potential of MSCs for drug-induced AKI.